2017
DOI: 10.1021/acsomega.7b01428
|View full text |Cite
|
Sign up to set email alerts
|

LaFexCo(1–x)O3Thin-Film Oxygen Reduction Catalysts Prepared Using Spray Pyrolysis without Conductive Additives

Abstract: LaFe x Co (1– x ) O 3 thin films were prepared on fluorine-doped tin oxide conducting glass substrates by spray pyrolysis without any conductive additives and evaluated for their ability to catalyze the oxygen reduction reaction. Onset potential and current density were found to be comparable to platinum, and the resulting crystallite size was on the order of 20 nm. Coordination of the precursor metal ions by ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Indeed, only by using perovskite single-material electrodes can the ORR mechanism occurring on the perovskite surface be studied. To date, a small number of researchers have published the ORR activity of perovskites without carbon and a few examples are given here. One way that perovskites have been successfully studied without carbon is by using epitaxial thin films. With physical vapor deposition techniques, the perovskite’s structure and composition can be precisely tailored.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…Indeed, only by using perovskite single-material electrodes can the ORR mechanism occurring on the perovskite surface be studied. To date, a small number of researchers have published the ORR activity of perovskites without carbon and a few examples are given here. One way that perovskites have been successfully studied without carbon is by using epitaxial thin films. With physical vapor deposition techniques, the perovskite’s structure and composition can be precisely tailored.…”
Section: Reaction Mechanismsmentioning
confidence: 99%
“…[6] , [58] Further, the XRD patterns of as-synthesized LaCo 0.2 Fe 0.8 O 3 and LaCo 0.4 Fe 0.6 O 3 were well matched with earlier published reference articles and JCPDS card nos. (88–0641 and 40–0224), respectively [59] , [60] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Kinetic measurements indicated that the as-prepared LFCO-FTO composite maintained as imilara ctivity to that of unsupported bulk Pt itself. [47] BMethanol oxidation reaction (MOR)…”
Section: La-basedsystems: Importance Of the B-sitecation Identitymentioning
confidence: 99%
“…In particular, a LaFe 0.4 Co 0.6 O 3 (LFCO) thin film was deposited onto FTO by means of spray pyrolysis, and the presence of an optically transparent FTO electrode enabled the observation of a reversible color change upon the application of a potential, thereby suggesting that the perovskite film could repeatedly and reversibly oxidize and reduce. Kinetic measurements indicated that the as‐prepared LFCO‐FTO composite maintained a similar activity to that of unsupported bulk Pt itself …”
Section: Applications In Direct Methanol Fuel Cellsmentioning
confidence: 99%